Live edge emerald green resin art side table / Nurul Basirah Md Ali - Md Ali, Nurul Basirah (2021)
Nowadays, the used of epoxy resin in furniture industry is not a new trend. However, there are still not many companies have involved in the used of epoxy resin as one of their raw materials. Epoxy resin is a chemical substance that need to be mixed with hardener to harden. This substance is suitable to use with wood since it can increase it appearance. Besides that, there are many other less known species in Malaysia such Juniper sp, that was used as the main material in this project. The objective of this research are to produce a product by using Juniper wood with the combination of epoxy resin. A set of question were distributed to 100 respondents regarding a few issues, which are the knowledge of raw material, design function, marketing, and the satisfaction on the Live Edge Emerald Green Epoxy Resin Art Side Table. Based on the result, most of all respondents were satisfied with the material, design, and marketing of the product. Thus, it can be concluded that all of them agreed that this product has a potential to be commercial in the market.